2019
DOI: 10.21203/rs.2.19369/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel five-gene signature for predicting prognosis in liver cancer

Abstract: Purpose Liver cancer is one of the most common malignant tumors in China, ranked 5th among the malignant common tumors in the world, which is still difficult to diagnose early and treat effectively. Therefore, exploring some indicators for prognostic prediction is imperative in the treatment of liver cancer. Methods Liver cancer data was obtained from The Cancer Genome Atlas (TCGA). We obtained differentially expressed genes (DEGs) by R software from TCGA database. Risk scores were acquired to assess the weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Yue et al discovered that LINC02154 promotes hepatocellular carcinoma proliferation and metastasis, by increasing SPC24 promoter activity and activating the PI3K-AKT signaling pathway (Yue et al, 2022). LINC02154 is a cancer-promoting factor not only in liver cancer but also in laryngeal squamous cell carcinoma (Zhang et al, 2019). Consistent with previous findings, the present study showed that LINC02154 was expressed at a high level in the hyperrisk category with a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Yue et al discovered that LINC02154 promotes hepatocellular carcinoma proliferation and metastasis, by increasing SPC24 promoter activity and activating the PI3K-AKT signaling pathway (Yue et al, 2022). LINC02154 is a cancer-promoting factor not only in liver cancer but also in laryngeal squamous cell carcinoma (Zhang et al, 2019). Consistent with previous findings, the present study showed that LINC02154 was expressed at a high level in the hyperrisk category with a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Among the 12 key FAM-related genes we finally screened for risk score modeling, most lncRNAs have not been studied, but some lncRNAs have also appeared in the construction of prognosis prediction models for different diseases. For example, AL390755.1 was used to construct a prognostic prediction model for low-grade glioblastoma, and similar LINC01281, AL589986.2, and AC007032.1 were also used for laryngeal cancer (Zhang et al, 2019), cervical cancer (Ye et al, 2021), dilated cardiomyopathy (Zhang et al, 2020) and proliferative vitreoretinopathy respectively (Ni et al, 2021), which were also considered a potential diagnostic marker. At the same time, we also noticed that GAS6-DT and TMPO-AS1 have been shown to have regulatory axes in previous studies, which can interact with another coding/non-coding RNAs, and these two lncRNAs were proved to be possible risk factors for LUAD in our PCR validation.…”
Section: Discussionmentioning
confidence: 99%